The analysis of Tin(IV) oxide prepared via hydrothermal treatment and ethanol gas sensing properties / Nurfarzana Mohd Noor and Vicinisvarri Inderan - Mohd Noor, Nurfarzana; Inderan, Vicinisvarri (2020)
Tin(IV) oxide SnO2 is a semiconductor material with a wide bandgap energy (3.6 eV). It is particular interesting, because it has high a thermal and chemical stability and high surface to-volume ratio. Tin(IV) oxide nanostructure can be synthesis using various of techniques such as sol-gel, electrospinning, thermal evaporation, and co-precipitation. They produce nanostructure, however, they involve expensive instrumentation and high operational temperature. Among them, the hydrothermal synthesis is widely used nowadays because of its simplicity process. This study was carried out to analyze the data of SnO2 nanostructures which was prepared via hydrothermal treatment at different heat treatment duration (6, 12, 18, and 24 hours) under constant temperature, 180 °C. The effect of different heat treatment duration on the structure, size and morphology was investigated by X-ray diffraction (XRD), Ultraviolet-visible spectroscopy (UV-vis), Field emission scanning electron microscope (FESEM), and Fourier-transform infrared spectroscopy (FTIR). It was found that the formation of SnO2 nanorods for all sample grew into closely packed flower-like nanostructures. The diameter of the SnO2 nanorods reduced from 43.30 to 24 .96 nm for heat treatment duration at 6 to 24 hours, respectively. For HRTEM analysis the diameter of SnO2 nanorods for 24 hours was approximately 22.89 ± 4.84 nm. For UV-vis analysis, it was observed that, the band gap energy increased (3.52, 3.56, 3.57 and 3.6 eV). In second part of study, the best prepared SnO2 sample was tested on ethanol gas at different operating temperature (200 °C - 450 °C). The highest sensor response (Ro/Rg ~ 1645.265) was obtained at temperature 450 °C. Therefore, the operating temperature with the highest sensor response was selected as the operating temperature.